Nefastus, comitialis, iuris coctior - neologizmy prawnicze w komedii Plauta Poenulus - Pieczonka, Joanna (Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych Uniwersytetu Wrocławskiego, 2012)
The article is devoted to the search by Plautus for Latin equivalents for originally Greek phrases. Plautus did not shy away from creating neologisms, thanks to which he was also able to engage in wordplay.
Keywords: Plaut; Poenulus; komedia rzymska; komedia hellenistyczna; neologizmy